2019
DOI: 10.1038/s41598-018-37522-6
|View full text |Cite
|
Sign up to set email alerts
|

MITF has a central role in regulating starvation-induced autophagy in melanoma

Abstract: The MITF transcription factor is a master regulator of melanocyte development and a critical factor in melanomagenesis. The related transcription factors TFEB and TFE3 regulate lysosomal activity and autophagy processes known to be important in melanoma. Here we show that MITF binds the CLEAR-box element in the promoters of lysosomal and autophagosomal genes in melanocytes and melanoma cells. The crystal structure of MITF bound to the CLEAR-box reveals how the palindromic nature of this motif induces symmetric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 56 publications
1
65
0
Order By: Relevance
“…Significantly ectopic expression of ASAH1 could rescue the cell cycle defects associated with MITF depletion, consistent with a role for ASAH1 in promoting melanoma proliferation (Realini et al 2016). Moreover, MITF in melanoma has recently been identified as a regulator of a subset of genes implicated in autophagy (Moller et al 2019), a lysosome-dependent process that degrades and recycles unwanted organelles and may represent a key survival strategy of cells under nutrient restriction. Notably, experimental depletion of MITF reduced the autophagy response to starvation, whereas overexpression of MITF increased the number of autophagosomes.…”
Section: Mitf Target Genes and Biological Rolementioning
confidence: 54%
“…Significantly ectopic expression of ASAH1 could rescue the cell cycle defects associated with MITF depletion, consistent with a role for ASAH1 in promoting melanoma proliferation (Realini et al 2016). Moreover, MITF in melanoma has recently been identified as a regulator of a subset of genes implicated in autophagy (Moller et al 2019), a lysosome-dependent process that degrades and recycles unwanted organelles and may represent a key survival strategy of cells under nutrient restriction. Notably, experimental depletion of MITF reduced the autophagy response to starvation, whereas overexpression of MITF increased the number of autophagosomes.…”
Section: Mitf Target Genes and Biological Rolementioning
confidence: 54%
“…Moreover, early evidence also indicated that deregulation of MITF expression or activity by oncogenes such as adenovirus E1A could lead to dedifferentiation (Dooley et al 1988;Wilson et al 1989;Yavuzer et al 1995). However, the role of MITF in melanoma and melanocytes has since been extended and now includes the regulation of genes implicated in several biological processes beyond differentiation such as survival (McGill et al 2002), cell cycle control Carreira et al 2005Carreira et al , 2006Garraway et al 2005), invasion (Carreira et al 2006;Cheli et al 2011Cheli et al , 2012, lysosome biogenesis (Ploper et al 2015;Zhang et al 2015b) and autophagy (Möller et al 2019), senescence bypass (Giuliano et al 2010), and DNA damage repair and chromosome stability (Giuliano et al 2010;Strub et al 2011). Since the role and regulation of MITF has recently been reviewed in depth (Goding and Arnheiter 2019), we only cover here the features of MITF expression and activity relevant for its association with specific melanoma phenotypic states.…”
Section: Mitf and Phenotype Switching In Melanomamentioning
confidence: 99%
“…MITF-regulated genes were, however, distinct from these activated by TFEB and TFE3 [121]. Modulating the level of MITF largely affected the response of melanoma cells to starvation-induced autophagy [121]. Considering an important role of MITF in the regulation of melanoma cell phenotype and response to targeted drugs, including diverse execution of MITF-dependent programs in drug-resistant melanoma cells [122][123][124], further research is necessary to delineate a relationship between activity of MITF and TFE transcription factors and consequences of manipulation of autophagy-lysosomal signaling in melanoma cells.…”
Section: Autophagy In Melanomamentioning
confidence: 88%
“…Interestingly, another transcription factor that is related to TFEB, microphthalmia-associated transcription factor (MITF) has been shown to bind to the promoters of genes encoding lysosomal and autophagosomal proteins in melanoma. MITF-regulated genes were, however, distinct from these activated by TFEB and TFE3 [121]. Modulating the level of MITF largely affected the response of melanoma cells to starvation-induced autophagy [121].…”
Section: Autophagy In Melanomamentioning
confidence: 99%